2014
DOI: 10.3177/jnsv.60.300
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Digestibility of Rice Prolamin/Protein Body-I Particle Is Decreased by Cooking

Abstract: Rice is a staple cereal and a major source of both protein and energy in most Asian countries. Thus, the true digestibility of cooked rice protein is very important for human nutrition. The proteins in rice endosperm consist mainly of storage proteins, e.g., glutelin, prolamin and globulin. Two major proteins, glutelin and prolamin, can be separated into several protein bands by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). Glutelin separates into three bands: proglutelin (57 kDa), an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
(14 reference statements)
2
12
0
Order By: Relevance
“…This condition might prove the hypothesis of Kubota et al. (), who suggested that cooking might lead to hydrophobic interactions and disulfide linkages in PB‐Is. Rice protein solubility in the solvent without urea was almost constant during cooking processes, suggested that changes of hydrogen bonds did not occur during cooking‐induced protein interactions despite its important role in the native structure of rice protein.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…This condition might prove the hypothesis of Kubota et al. (), who suggested that cooking might lead to hydrophobic interactions and disulfide linkages in PB‐Is. Rice protein solubility in the solvent without urea was almost constant during cooking processes, suggested that changes of hydrogen bonds did not occur during cooking‐induced protein interactions despite its important role in the native structure of rice protein.…”
Section: Resultssupporting
confidence: 81%
“…Kubota et al. () also reported that rice prolamin indigestibility was associated with PB‐I, which could be degraded or weakened by alkali, and thus increased protein digestibility of rice prolamin (Kubota et al., ). Therefore, in the present study, the hydrolysis of the 16 kDa prolamin might be due to the IEF buffer corrosion on PB‐I structure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations